Transforming early language learning: Augmented reality flashcards for enhancing English vocabulary for young learners - Erwin Rahayu Saputra; Seni Apriliya; Dwi Alia; Karmila Rafiqah Binti Mohd Rafiq Anbarasan; Zahara Fajriati Nizar (Studies in English Language and Education, 2026)
With the prevalence of digital technologies worldwide, their inclusion to increase student motivation and comprehension in English vocabulary, especially at the elementary level, is an important factor. This paper aims to explore how to develop Augmented Reality (AR)-based learning media as a fun tool for learning vocabulary. This study focuses on developing an AR-based flashcard that uses three-dimensional (3D) visualization and native-speaker audio for pronunciation to help elementary learners master English vocabulary and increase engagement. Applying a Research and Development (R&D) approach with the ADDIE model, five systematic phases (needs analysis, design, development, implementation, and evaluation) involving diverse participants (students, teachers, and experts) and multiple methods (interviews, surveys, expert validation, and classroom observations) were conducted. The result shows that AR-based flashcards can enhance students’ vocabulary mastery by providing interesting and engaging 3D content and native-speaker audio pronunciation as sensory enhancements. This innovative research on the combination of an interactive 3D visualization and an audio supplement provides students with more effective assistance in mastering English vocabulary. Furthermore, this research can serve as a reference for developing innovative, technology-driven learning tools that address current educational needs. The result indicates that AR-based learning media can be used effectively to enhance students’ motivation to learn English vocabulary, thereby improving their learning outcomes in the early stages of language education.